Broadcasting in 2030: Crystal Gazing - Srivastava, Aprajita; Srivastava, Hari Om (European Journal of Applied Sciences, 2021)
Broadcasting has informed, educated and entertained the world population during last 120 years of its inception. There has been lot of technical evolution during this period namely coming of digital and compression technologies, emergence of satellite, internet and fiber optics adding to the earlier terrestrial mode of transmission and providing simplex to duplex mode and interactivity. This has also led to any person becoming a broadcaster using her/his smart phone and the social media like YouTube, Instagram, Facebook etc. apart from tens of thousands of DTH channel operators. In this scenario, the content called king, has suffered most, losing its appeal, integrity, reliability and ethics. Authors feel that by 2030, this will lead to the closure of most of the Public Broadcasting services, News Channel and unethical content broadcasters on social media. Only A few bigger global delivery companies will possess the skill and finances to harness the potential of interactive and enhanced TV (ITV and ETV) which shall permit the users to view or skip a program or commercial. “There are decades where nothing happens; and there are weeks where decades happen.” ― Vladimir Ilyich Lenin